Interpreting risk reduction in clinical trials for pulmonary arterial hypertension. (16th May 2018) - Lajoie, Annie C.; Bonnet, Sébastien; Lacasse, Yves; Lega, Jean-Christophe; Provencher, Steeve
Because of scepticism concerning study results when relying solely on relative effect estimates, the number needed to treat (NNT) has been used extensively to quantify the net clinical benefit of an intervention, and is reported increasingly in randomised trials and observational studies. This method is a simple measure representing the number of patients who would need to be treated to prevent one additional adverse event. However, like relative risk, the NNT is an inherently time-dependent measure. Thus, its calculation may lead to misleading interpretations, especially for studies involving varying follow-up times or recurrent outcomes. In addition to study duration and the efficacy of the therapy and the comparator, multiple other factors directly influence the NNT and should be taken into account in its interpretation as for comparative effectiveness of therapies. Its accurate estimation and interpretation, as well as its limitations, are therefore crucial to avoid erroneous clinical and public health decisions. We discuss the calculation and the interpretation of risk reduction and the NNT in the context of the changing landscape of clinical trials in pulmonary arterial hypertension. Number needed to treat is widely used in clinical trials, but many factors influence its appropriate interpretation http://ow.ly/lMuS30jAwPJ